55 Provision of cardiac CT angiography services within the irish public health service. (16th October 2019) - Giblin, G; McAdam, BF
Abstract : Background: The 2016 guidelines from the UK National Institute for Health and Care Excellence recommend computed tomography (CT) coronary angiography as the first-line investigation for stable chest pain. Currently the scale of provision of cardiac CT within the Irish public health system is unknown. Aims: The aims of this study were (1) to assess the provision of cardiac CT services within the Irish public health service between 2016 and 2018, (2) determine regional variation in provision of this service, (3) describe current cardiac CT scanner infrastructure, (4) estimate the capacity increase required to implement the NICE guidelines and (5) determine whether there are sufficient qualified Cardiologists and Radiologist to implement a dedicated service. Methods: The Radiology departments of public hospitals accepting acute adult medical patients in the Republic of Ireland were surveyed for the numbers of CT coronary angiography performed per year between 2016 and 2018. Many private hospitals, particularly in Dublin, provide some cardiac CT capability by outsourcing from public hospitals but this data was not available. The four CT manufacturers provided information on location and cardiac specifications of their scanners. Results: There are currently 23 cardiac enabled CT scanners (64 slice or greater) within the 30 public service hospitals surveyed (77%), with a further 10 hospitals having scanners with cardiac capability (requiring a software upgrade) while four of the hospitals have a CT scanner with a fully enabled cardiac package but are currently not performing cardiac studies. Thirteen of the surveyed public hospitals (43%) currently provide a cardiac CT service. Two further hospitals provide a CT calcium scoring service without CT angiography. The crude national rates of cardiac CT angiography were 1423, 1579 and 1677 scans for 2016–2018 respectively, equating to a mean annual rate of 33 scans per 100, 000 population based on 2016 Census data compared to the estimated UK NHS rate of 66/100, 000, although many scans are referred to private hospitals, mostly in Dublin. When examined for regional variation by province, mean annual rates/100, 000 population were 12.37 for Munster, 25.27 for Connaught, 29.49 for Leinster excluding Dublin and 65.51 for the Dublin region (figure 1 ). The BSCI estimate a CT rate of 523/100, 000 to implement the NICE guidelines. Extrapolating this to the Republic of Ireland would require an increase in rates of approximately 1484% to deliver guideline directed care within the public health service. Moreover, there are only 15 radiologists and 14 cardiologists with expertise in reporting cardiac CT practising within the Irish public system resulting in a substantial deficiency in trained doctors to provide this service. Currently, co-reporting by Radiology and Cardiology is the norm. Conclusions: Cardiac CT rates within the Irish public health service are approximately 50% of published UK rates. There is marked regional variability in the provision of cardiac CT with large areas having no access within the public health service unless outsourced to private institutions. Access to scanner time and lack of appropriately trained practitioners are barriers to improved service delivery if Ireland intends to model service provision on the NICE guidelines. An increase in collaborative public-private partnerships may be required to improve patient access to this imaging service.